Pengaruh Aplikasi Biostimulant terhadap Pertumbuhan dan Produksi Selada (Lactuca sativa L.) - Primarine R Tahapary; Herman Rehatta; Henry Kesaulya (JURNAL BUDIDAYA PERTANIAN, 2020)
Lettuce is a type of vegetable that is very popular with the people of Indonesia. It contains healthy nutrients including minerals, vitamins, antioxidants, potassium, iron, folate, carotene, vitamin C and vitamin E. Biostimulants has the ability to stimulate new root formation, improve plant root systems, increase the number of tillers, and increase yield. Biostimulant concentration and site of administration play a role in providing nutrients for the needs of lettuce plants. To obtain the right concentration and place of administration for the growth and yield of lettuce, the experiment was carried out using a 2-factor Randomized Block Design. The first factor was the concentration of biostimulants (K) with 6 levels of concentration including: K0 (without giving biostimulants), K1 (giving biostimulants at a concentration of 1 mL/L of water), K2 (giving of biostimulants at 2 mL/L of water), K3 (giving biostimulants at 3 mL/L of water). K4 (giving biostimulant at 4 mL/L water), K5 (giving biostimulant at 5 mL/L water). The second factor was the site of administration (T), namely: T1 (through the leaves) and T2 (through the soil). The interaction between biostimulant concentration and administration gave a very significant effect on leaf number, crop fresh weight, root length and root number. Biostimulant concentration (K) gave the percentage of plant growth in the variables of plant height (34.29%) and leaf area (47.34%). Place of administration (T) gave percentage of plant growth the variables of leaf area (21.08%) and root wet weight (0.52%). The interaction of biostimulant concentration and administration place (K x T) gave the percentages of plant growth variables of leaf number (15.5%), plant fresh weight (52.33%), root dry weight (2.30%), root length (16.53%), and root number (108.5%). The best treatment in this study was the provision of biostimulant at a concentration of 2 mL/L of water that was given through leaves. Keywords: administration place, biostimulant, concentration, growth and production, lettuce ABSTRAK Selada merupakan jenis sayur yang sangat digemari oleh masyarakat Indonesia serta mengandung nutrisi yang sehat, yang meliputi mineral, vitamin, antioksidan, potassium, zat besi, folat, karoten, vitamin C dan vitamin E. Biostimulan mampu merangsang pembentukan akar baru, memperbaiki sistem perakaran tanaman, memperbanyak jumlah anakan, dan meningkatkan produksi tanaman. Konsentrasi biostimulan dan tempat pemberian merupakan interaksi yang berperan dalam menyediakan unsur hara bagi kebutuhan tanaman selada. Untuk memproleh konsentrasi dan tempat pemberian yang tepat bagi pertumbuhan dan produksi tanaman selada, dilakukan percobaan dengan menggunakan Rancangan Acak Kelompok 2 faktor. Faktor pertama adalah pemberian biostimulan (K) dengan 6 taraf konsentrasi meliputi: K0 (tanpa pemberian biostimulan), K1 (pemberian biostimulan dengan konsentrasi 1 mL/L air), K2 (pemberian biostimulan 2 mL/L air), K3 (pemberian biostimulan 3 mL/L air), K4 (pemberian biostimulan 4 mL/L air), K5 (pemberian biostimulan 5 mL/L air). Faktor kedua adalah tempat pemberian (T), yaitu: T1 (melalui daun) dan T2 (melalui tanah). Interaksi konsentrasi biostimulan berpengaruh sangat nyata terhadap variabel jumlah daun (helai), bobot segar tanaman (g), panjang akar (cm) dan jumlah akar (helai). Pada konsentrasi biostimulan (K) memberikan persentasepertumbuhan tanaman pada variabel tinggi tanaman (34,29%) dan luas daun (47,34%), Tempat pemberian (T) memberikan persentasepertumbuhan tanaman pada variabel luas daun (21,08%), bobot basah akar (0,52%), serta interaksi konsentrasi biostimulan dan tempat pemberian (KT) memberikan persentasepertumbuhan tanaman pada variabel jumlah daun (15,5%), bobot segar tanaman (52,33%), bobot kering akar (2,30%), panjang akar (16,53%), serta jumlah akar (108,5%). Perlakuan terbaik dalam penelitian ini adalah pemberian biostimulan konsentrasi 2 mL/L air dan diberikan melalui daun. Kata Kunci: biostimulan, konsentrasi, pertumbuhan dan produksi, selada, tempat pemberian,